1995
DOI: 10.1088/0953-8984/7/30/005
|View full text |Cite
|
Sign up to set email alerts
|

Lattice dynamics and related diffusion properties of intermetallics: I. Fe3Si

Abstract: Abslrad. The phonon dispersion of iron-rich FBSi alloys of DO3 struclwe (space gmup F m -3m) has been studied by inelastic neulron scaltering. The mea~wements were carried out on two crystals of different composition: Fe7,Siz at 20 and 930°C. and FesoSilo at 20. 930 and IIOO'C. The respective degree of order was determined by powder diffraction measurements. A general decrease of phonon frequencies with increasing temperature is found. the temperature dependence being strongest for lransvene phonons with IB50]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…The three different methods give almost the same phonon dispersion curves, with the exception of the PAW GGA-PBE method that results in a slightly smaller acoustic frequency at the X point. For Fe 3 Si, good agreement is obtained for the acoustic frequencies among all of the calculation methods and the experimental values [76]. However, at the higher frequency regions, the PAW methods predict larger frequencies in comparison with experimental data.…”
Section: Enthalpy Of Formationmentioning
confidence: 56%
“…The three different methods give almost the same phonon dispersion curves, with the exception of the PAW GGA-PBE method that results in a slightly smaller acoustic frequency at the X point. For Fe 3 Si, good agreement is obtained for the acoustic frequencies among all of the calculation methods and the experimental values [76]. However, at the higher frequency regions, the PAW methods predict larger frequencies in comparison with experimental data.…”
Section: Enthalpy Of Formationmentioning
confidence: 56%
“…From quantum mechanical perturbation theory we expect the first-order lineshape broadening to originate with the cubic term in the potential, and this is calculated to be linear in T . Such behavior is sometimes reported, but at higher temperatures the broadening often increases faster than T 1 (e.g., [333]). Perhaps this can be understood as follows.…”
Section: Anharmonic Trends Of Fcc and Bcc Metalsmentioning
confidence: 83%
“…The curve for Grossularite shows a particularly striking increase above the harmonic curve (and the classical limit), but it may indicate a change in defect density or another structural change in the material. Studies of phonons in Fe 3 Si alloys at temperatures of 20, 930, and 1100 • C showed large phonon broadenings, approximately proportional to phonon wavevector [333]. These broadenings were interpreted as effects of chemical disordering in this material, which undergoes an order-disorder transformation at elevated temperatures.…”
Section: Anharmonicity and Heat Capacitymentioning
confidence: 93%
“…This model was first applied successfully to pure fcc and bcc metals and recently to intermetallic compounds Fe 3 Si [14] and Fe 1−x Al x [15] with the D0 3 and B2 structures. In this model, the migration energy is derived from the following relation:…”
Section: Migration Energy Calculationmentioning
confidence: 99%
“…In pure fcc metals, excellent agreement between calculated and measured values of E M was found, whereas in bcc metals, where the experimental values are less well known, predictions were obtained that show a pronounced chemical group systematics. More recently the same method has been used by Randl et al [14] in Fe 1−x Si x and Kentzinger et al [15] in Fe 1−x Al x alloys to estimate the migration energies. Strictly speaking, this method to determine E M is valid only for monoelemental structures.…”
Section: Introductionmentioning
confidence: 99%